Językowo-kulturologiczne prawdy o lubuskich miodach (na podstawie wybranych kulinarnych opracowań poświęconych regionalnym specjałom Ziemi Lubuskiej) = Linguistic-culturological truths about honeys of the Ziemia Lubuska region (based on selected culinary guides on the specials of the area) - Węgorowska, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Honey, metaphorically-symbolically also called "liquid gold" and "Nature`s golden miracle", has been a human`s companion from the dawn of time. This natural biopreparation is firmy inscribed in the history of Ziemia Lubuska and is crrently perceived as its regional product.
Keywords: miód; miody lubuskie; Ziemia Lubuska; lingwokulturologia; honey; honeys of Ziemia Lubuska; linguoculturology